Computational Design of an Energy-Efficient Small Axial-Flow Fan Using Staggered Blades with Winglets - Mustafa Tutar; Janset Betul Cam (International Journal of Turbomachinery, Propulsion and Power)
The present study introduces a conceptual design of a small axial-flow fan. Both individual and combined effects of blade stagger angle and winglet on the performance of the fan design are investigated in design and off-design operating conditions using a computational flow methodology. A stepwise solution, in which a proper stagger angle adjustment of a specifically generated blade profile is followed by appending a winglet at the tip of the blade with consideration of different geometrical parameters, is proposed to improve the performance characteristics of the fan. The initial model comparison analysis demonstrates that a three-dimensional, Reynolds-averaged Navier–Stokes (RANS) equation-based renormalization group (RNG) k–ε turbulence modeling approach coupled with the multiple reference frame (MRF) technique which adapts multi-block topology generation meshing method successfully resolves the rotating flow around the fan. The results suggest that the use of a proper stagger angle with the winglet considerably increases the fan performance and the fan attains the best total efficiency with an additional stagger angle of +10° and a winglet, which has a curvature radius of 6.77 mm and a twist angle of −7° for the investigated dimensioning range. The present study also underlines the effectiveness of passive flow control mechanisms of the stagger angle and winglets for energy-efficient axial-flow fans.